The Utilization of Digital Media in Increasing Student Learning Motivation - Nurrahman, Muhammad Fahmi; Hafidz, Hafidz (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
The use of digital media in learning has the potential to increase students' motivation to learn, but the impact does not appear automatically just because learning uses technology. The literature shows that the influence of digital media on motivation is more determined by the quality of learning design, the suitability of activities with students' learning needs, and the readiness of educators and school support. This study aims to summarize research findings on the mechanisms of digital media in strengthening learning motivation, the types of media that are often reported to be effective, the remaining empirical evidence gaps, and implementation challenges in the field. The method used is a qualitative literature review with thematic content analysis of relevant journal articles and supporting sources that strengthen the conceptual foundation. The results of the synthesis show that digital media tends to increase motivation when learning is designed interactively, provides quick feedback, provides a clear learning structure, and encourages active participation through collaboration and production of works. The Learning Experience Design (LXD) approach emphasizes that improving digital learning experiences through easy navigation, directed activity flows, and self-regulation support contributes to strengthening self-efficacy, task value, and self-regulation (Wong & Hughes, 2023). On the other hand, the findings across studies also confirm challenges in the form of access inequalities, technical constraints, variations in teachers' digital competencies, as well as the risk of distraction and privacy issues in the use of certain platforms (Wang & Tahir, 2020; González-Mohíno et al., 2024; Özdemir, 2025). This study emphasizes the need for digital media integration as a context-based pedagogical project, not just a platform selection, while encouraging the strengthening of evidence at the elementary-high school level and standardization of motivation measurement so that research conclusions are stronger and more applicable. Keywords: Digital media, Learning motivation, Learning engagement, Learning experience design